2015
DOI: 10.1070/qe2015v045n06abeh015516
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of intense laser radiation through a diffusion flame of burning oil

Abstract: It is shown that for a class of models having Goldstone modes, any single-site theory must predict unphysical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The measurements of the flame temperature under the conditions of laser beam propagation have shown that in the range of intensities 3.5·10 4 -10 5 W/cm 2 the temperature linearly grows from 2000 to 3000 K. With a further increase in intensity, the temperature rise becomes slower, and at the maximal value of I in = 1.2·10 6 W/cm 2 the temperature becomes equal to 3400 K. For qualitative interpretation of the data presented in figure 3 let us restrict ourselves to considering the influence of solid carbon particles on the radiation transmission [4]. These particles are always present in the hydrocarbon flame in the form of soot [5].…”
Section: Attenuation Of Laser Radiation By the Diffusion Flame Of Burmentioning
confidence: 99%
“…The measurements of the flame temperature under the conditions of laser beam propagation have shown that in the range of intensities 3.5·10 4 -10 5 W/cm 2 the temperature linearly grows from 2000 to 3000 K. With a further increase in intensity, the temperature rise becomes slower, and at the maximal value of I in = 1.2·10 6 W/cm 2 the temperature becomes equal to 3400 K. For qualitative interpretation of the data presented in figure 3 let us restrict ourselves to considering the influence of solid carbon particles on the radiation transmission [4]. These particles are always present in the hydrocarbon flame in the form of soot [5].…”
Section: Attenuation Of Laser Radiation By the Diffusion Flame Of Burmentioning
confidence: 99%